Use of rivaroxaban in Germany: a database drug utilization study of a drug started in hospital - Jobski, Kathrin (Springer Berlin Heidelberg, 2014)
PURPOSE: The purpose of this drug utilization study was to describe the use of rivaroxaban in Germany during a time period in which approval was limited to the prevention of venous thromboembolism following hip or knee replacement. Additionally, we explored the feasibility of reconstructing inpatient drug use of rivaroxaban in a database where with a few exceptions inpatient prescribing information is not available. METHODS: Source of data was one statutory health insurance providing data on about seven million insurants throughout Germany. Analyses were based on a cohort of rivaroxaban users from launch (October 2008) to December 2009 and encompassed potential indications for rivaroxaban use, treatment duration, and co-prescribing of potentially interacting drugs. Start of rivaroxaban treatment was defined by the date of surgery. RESULTS: During the study period, 425 rivaroxaban users were identified contributing 440 treatment periods. For more than 82 % of these episodes labelled indications could be determined. Treatment durations exceeded recommendations in 95 % of the episodes following knee replacement whereas rivaroxaban use after elective hip surgery was found to be longer than recommended in 56 %. Prescribing of potentially interacting medication was rare except for non-steroidal anti-inflammatory drugs. CONCLUSIONS: Overall, no important off-label use of rivaroxaban was identified. Based on several assumptions that have to be considered in the interpretation of the results our study describes a database approach to reconstruct inpatient drug use for a drug started after a coded hospital procedure, when treatment continues after hospital discharge and no change in drug use is expected in the outpatient setting. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00228-014-1697-7) contains supplementary material, which is available to authorized users.